SUB-RETINAL FLUID (SRF) AS A PROTECTIVE FACTOR AGAINST MACULAR ATROPHY AND POSITIVE RETINAL BIOMARKER OF VISUAL OUTCOME - Kjaeva, Jana Nivichka; Shekerinov, Natasha Trpevska; Isjanovski, Igor; Petrushevska, Andrijana; Memedi, Gazmend (Journal of Morphological Sciences; Vol 8 No 1 (2025): JMS, 2025)
Age related macular degeneration is the leading cause of legal blindness in elderly people. Its prevalence increases significantly after the age of 50. Neovascular, exudative AMD accounts for less than 10% of cases, the wet form (nAMD) is responsible for the largest number of cases where severe central visual impairment occurs compared to the dry form of AMD. Neovascular AMD form is characterized by the growth of abnormal choroidal new blood vessels from pre-existing choriocapillaris vessels. The exudation resulting from the immaturity of the blood vessels resulting in accumulation of fluids in different retinal compartments depending on the MVN (macular neovascular ) extension and localization. Subretinal fluid is an exudation that is localized in the space between the neurosensory retina and the retinal pigment epithelium.  VEGF-A plays a key role in the process of angiogenesis and vascular permeability. Anti-vascular endothelial growth factor (anti-VEGF) therapy currently plays a central role in the treatment of numerous retinal diseases, most notably exudative age-related macular degeneration (eAMD), diabetic retinopathy and retinal vein occlusions, offering significant functional and anatomic benefits in most of the patients. Of all retinal biomarkers subretinal fluid (SRF) is the only imaging biomarker, that is, the only "pathological" morphological parameter that is consistently associated with a positive effect on visual acuity and has protective role against development of macular atrophy. Kew words:  wet AMD, sub-retinal fluid, anti-VEGF treatment, macular atrophy.